Huntington S Disease in Chile: Epidemiological and Genetic Aspects - Chana-Cuevas, P; Rojas, N (S. Karger AG, 2023)
Introduction: Huntington s disease (HD) is a neurodegenerative, autosomal dominant disabling condition due to an expansion of the CAG trinucleotide in the HTT gene. Motor, psychiatric, and cognitive disorders characterize it. Chilean reports on HD in the era of molecular diagnosis were wanted. Methods: This is a retrospective analysis of a prospective cohort of patients with HD seen at the Center for Movement Disorders (CETRAM) in Chile between 2013 and 2019. Sociodemographic, genotype, and neuropsychiatric features were investigated. Results: One hundred three probands with HD were identified. The majority (63.1%) were born in the metropolitan region, followed by the VIII and V regions with 8.73% and 7.76%, respectively. When pedigrees were analyzed, ninety unrelated families encompassing 1,007 individuals were identified; among relatives, other 35 manifested HD, and 106 died of HD. Besides, five hundred seventy-nine individuals were at genetic risk. The minimum estimated prevalence of HD in Chile in 2019 was 0.72 × 100,000 inhabitants. The mean CAG repeats (CAGR) of 47.2 ± 10.74 for the expanded allele and 17.93 ± 2.05 for the normal allele. The mean age of onset was 41.39 ± 13.47 years. Juvenile cases represented 7.8% of this cohort, and 4.9% had a late onset. There was a negative correlation between the age of onset and the CAGR of the expanded allele (r =-0.84 p < 0.0001). Besides, 79.6% had a family history of HD. Conclusions: This is the first report characterizing genetics, motor, and neuropsychiatric features in patients with HD in Chile. The mean length of CAGR expansion of the abnormal allele was similar to previous reports in North America (i.e., Mexico and Canada) and higher than that reported in the neighboring country of Argentina. According to previous estimations, the minimal prevalence of HD in Chile may be lower than expected. © 2023 S. Karger AG. All rights reserved.